Novel brominated lipidic compounds from lichens of central Asia - Rezanka, T; Dembitsky, V (Phytochemistry, 1999)
The composition of novel brominated aliphatic compounds from lichens collected during summer from stones around the lake Issyk-Kul (Central Asia) is described. The compounds, predominantly fatty acid derivatives with unique groups (bromine, cyclopropane, oxirane) and conjugated double and triple bonds, were identified by means of 1H and 13C-NMR, MS, IR and UV spectra.
Keywords: lipidy; spektrální analýza; Molecular Structure; molekulární struktura; lišejníky; Spectrum Analysis; Bromine; Lichens; Lipids; brom